The Impact of Environment, Communication, and Motivation on Employee Performance: Pengaruh Lingkungan, Komunikasi, dan Motivasi Terhadap Kinerja Karyawan - Febrianti, Shela; Adji Kusuma, Kumara (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the impact of the work environment, communication, and motivation on employee performance at PT. Harapan Sejahtera Karya Utama's production department. Utilizing quantitative methods and a sample of 169 employees, data was collected through questionnaires and analyzed using SPSS 22. Results indicate that these factors individually and collectively influence employee performance significantly. Specific aspects such as lighting, security, clear communication, teamwork, achievement rewards, career opportunities, and a sense of belonging positively affect performance. The findings underscore the importance of creating supportive work environments and implementing motivational strategies to enhance productivity and product quality, ultimately benefiting organizational success and profitability. Recommendations include aligning job roles with employee abilities to uphold product quality and increase company profits. Highlights: 1. Examining work environment, communication, motivation impact on employee performance.2. Significant influence found, emphasizing supportive environments and motivational strategies.3. Recommendations include aligning job roles to enhance productivity and profitability. Keywords: Work Environment, Communication, Motivation, Employee Performance, Quantitative Methods